Pengembangan Media Pembelajaran Interaktif Menggunakan Metode Ivers & Barron - Abdillah, T. Rafli (Jurnal Tika, 2022)
The presence of information technology and its various products has made it easier for humans to access various information, including knowledge. The rapid advancement of technology makes access to this information simple and quick. During the Covid-19 pandemic, the learning model shifted from traditional face-to-face learning to an online learning model. The change in the learning model serves as the backdrop for the development of learning media in this study, with the goal of creating interesting interactive learning multimedia. The method used in this research is Research and Development, as well as the Ivers and Barron method, which uses four stages to develop an interactive learning knowledge of vegetative plant growth processes, namely Decide, Design, Develop, and Evaluate. The study's findings include the use of interactive learning media learning media about the process of vegetative growth that is multimedia-based, complete with animations created with Adobe Flash tools, and that can be run on devices that support Adobe Flash Player. According to the test results, this application can run well on devices running the Windows operating system by running files with an.exe extension obtained during the compilation process of the entire multimedia development project file for interactive vegetative plant development